2020
DOI: 10.14202/vetworld.2020.2395-2400
|View full text |Cite
|
Sign up to set email alerts
|

Circulation of oxytetracycline- and ciprofloxacin-resistant commensal Escherichia coli strains in broiler chickens and farm environments, Bangladesh

Abstract: Background and Aim: The emergence of antimicrobial resistance (AMR) in commensal organism, such as Escherichia coli of food animals, is an alarming issue for global health. It increases the possibility of transmitting AMR determinant(s) to human bacterial pathogens by transferable genetic materials, particularly by plasmids. Hence, it is important to know which resistant genes are being carried by commensal organisms in food chain in a country and their level of temporal loads. As a result, pre-emptive measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Antibiogram profiling of all 425 isolates showing maximum resistance against tetracycline is corroborative with the previous findings in Bangladesh ( 30 ), Iran ( 31 ), Malaysia ( 32 ), and Egypt ( 33 ). The resistance of poultry origin -Enterobacteriaceae to quinolone antibiotics (ciprofloxacin) from South China ( 34 ), Spain ( 35 ), and Egypt ( 36 ) was also reported, where co-resistance to ciprofloxacin and tigecycline was reported.…”
Section: Discussionsupporting
confidence: 88%
“…Antibiogram profiling of all 425 isolates showing maximum resistance against tetracycline is corroborative with the previous findings in Bangladesh ( 30 ), Iran ( 31 ), Malaysia ( 32 ), and Egypt ( 33 ). The resistance of poultry origin -Enterobacteriaceae to quinolone antibiotics (ciprofloxacin) from South China ( 34 ), Spain ( 35 ), and Egypt ( 36 ) was also reported, where co-resistance to ciprofloxacin and tigecycline was reported.…”
Section: Discussionsupporting
confidence: 88%
“…The detection of tetA gene in all the E. coli isolates exhibiting resistance to oxytetracycline suggests that tetA might be responsible for developing resistance to oxytetracycline where the contributions of other two genes, tetB, and tetC might be little. However, this result was almost similar to Das [ 27 ] who showed that 35% E. coli isolates harbored the tetA gene showing resistance to oxytetracycline. There were 16 reported tet genes.…”
Section: Author's Point Of Viewssupporting
confidence: 87%
“…E. coli isolates from apparently healthy broiler chicken were found 100% resistant to ampicillin and tetracycline followed by sulfamethoxazole–trimethoprim (95%) and nalidixic acid (92%) [ 39 , 42 ]. The commonly detected oxytetracycline resistant genes were tetA, tetB and tetC gene [ 38 ]. Another study reported 55% prevalence of Extended-Spectrum Beta-Lactamase (ESBL)-producing E. coli in broiler ceca and feces at households, farms, and live poultry markets.…”
Section: Resultsmentioning
confidence: 99%